Evaluation of the effects of the body on athletes’ emotions and motivational behaviors from the perspective of big data public health - Zhang, Qiang; Lian, Diandong; Zhang, Yiqiao (Frontiers in Psychology, 2025)
ObjectiveAn analysis was conducted on the impact of the body on athletes’ emotions and motivation from the perspective of Public Health (PH).MethodsPSO-KNN (Particle Swarm Optimization-K-Nearest Neighbor) algorithm and PSO-SVM algorithm (Particle Swarm Optimization-Support Vector Machine) were obtained by combining Particle Swarm Optimization (PSO), K-Nearest Neighbor (KNN), and Support Vector Machine (SVM), and then the recognition rates of the two algorithms were compared.ResultsWhen comparing the PSO-KNN algorithm and PSO-SVM algorithm on baseline removed and baseline not removed, the average recognition rates of PSO-KNN algorithm and PSO-SVM algorithm under emotional state were 56.66 and 54.75%, respectively. The average recognition rates of PSO-KNN algorithm and PSO-SVM algorithm with baseline removal under tension were 53.16 and 50.58%, respectively.ConclusionThe algorithm that removes the baseline is better than the algorithm that does not remove the baseline, and the PSO-KNN algorithm is better than the PSO-SVM algorithm.